Following the issue-attention cycle of North Atlantic right whale science, conservation, and policy in six US newspapers: 2023 and 2024 - Marcus Reamer; Elise Rivera (Environmental Research Communications)
News media play an important and influential role in socioecological systems and environmental politics, in part because industry norms, practices, and timelines do not always align with conservation needs or objectives, and because these publications serve as political arenas where stakeholders compete for inclusion and the opportunity to frame topics to serve their interests. This study continues recent research regarding the issue-attention cycle (IAC) about North Atlantic right whale (NARW) science, conservation, and policy by using content and critical discourse analyses to code and analyze 107 texts published in six of the largest US newspapers in 2023 and 2024. We combined these results with data from 2010 to mid-March 2023 to contextualize the new findings. Our results revealed a strong negative correlation ( r = −0.88, p < .001) between right whale population estimates and media coverage in the six sampled newspapers. Coverage peaked in 2023 after Congressional action in late 2022 to delay fishery regulations as part of a USD $1.7 trillion omnibus spending bill. After that inflection point in the conservation conflict that media previously centered on, coverage decreased and the media narrative fragmented, shifting from centralized debates about new or stricter fishing regulations to more episodic reporting on whale births, injuries, and deaths. NARWs were also mentioned in coverage about other environmental topics, with a focus on offshore wind energy development. We argue that the IAC about NARW science, conservation, and policy has entered its fourth of five stages: gradual decline of public interest. NARW science, conservation, and policy may continue to receive media attention even in the later stage of the IAC, though it is likely that communicators may experience more editorial resistance and policy change and organizational action will be more difficult to achieve. This study highlights how media organizations use dramatization and problematization to draw public attention to topics, which does not always align with the timelines and needs of conservation and sustainability efforts. These results have direct implications for ongoing communication, outreach, and advocacy for NARW science, conservation, and policy, emphasizing the need for innovative, evidence-based strategies and tactics. By contextualizing the media’s role in shaping public discourse and environmental politics, this study also offers methods and insights that may be relevant to other conservation and sustainability topics across cultures and geographies.